OPTIMIZATION OF AGRICULTURAL ZAKAT: STUDY ON IMPLEMENTATION OF ZAKAT CORE PRINCIPLES IN BAZNAS MAJALENGKA REGENCY - Nuraeni Nuraeni; A Jajang Warya Mahri; Rida Rosida; Muhamad Rafi Anggara (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
The purpose of this study is to determine the priority problems and solutions for optimizing zakat receipts for agricultural products at BAZNAS Majalengka Regency. The research method used is descriptive quantitative by analyzing the responses to the questionnaire distributed to seven expert respondents from the fields of academia, practitioners and regulators. Based on previous research, four aspects were determined from the problem dimension and the solution dimension, namely the literacy aspect, the management aspect, the regulatory aspect, and the institutional aspect. The analysis process uses the Analytic Network Process (ANP) tool via the Super Decision 3.2 application. The results showed that the problem that became a priority was the aspect of literacy which showed that the receipt of zakat from agricultural products was not optimal because the level of community literacy was still low with a GmK value of 0.3518. Likewise with priority solutions in the aspect of literacy where education and outreach regarding zakat on agricultural products is still very much needed by the community with a GmK value of 0.3766.